The paradox of flash sales: How time-limited offers influence impulsive buying tendency in the emerging market (e-Commerce in Jakarta, Indonesia) - Christian Haposan Pangaribuan; Meisya Wanda; Sentot Basuki Prayitno; Tri Wismiarsi; Erland Barlian; Nathania Ferinda Roemawi (Jurnal Manajemen dan Pemasaran Jasa, 2025)
The shift to online shopping, especially in Indonesia, appeals to many people due to its easy access and promotions like big discounts and free shipping. The rapid growth of e-commerce supports this phenomenon, which in turn leads to an increase in impulsive buying habits and the popularity of flash sales programs. The aim of this study is to find out how price discounts, flash sale programs, and consumer trust affect impulsive buying tendency during flash sale programs. In this respect, we performed a survey on the 214 young participants in Jakarta, Indonesia. Questionnaires were used for primary data collection. To ascertain the validity and reliability of the questionnaire, a pre-test was conducted. This study used PLS-SEM to test the direct and mediating effects of attitude toward flash sales and consumer trust. The study finds that while consumer trust and price discounts do not directly influence impulsive buying, a positive attitude toward flash sales programs significantly mediates between price discounts and impulsive buying. The results demonstrate that price discounts have a greater influence on attitude toward flash sales than on consumer trust. The findings provide important insights for companies looking to implement discount strategies and offer potential avenues for future research.